ANALYSIS OF THE ROLE OF ISLAMIC EDUCATION IN PREVENTING RADICALISM AMONG YOUNG PEOPLE - Amal Fathullah; M. Nur Effendi; Muhammad Yusuf (Indonesian Journal of Education (INJOE), 2025)
The phenomenon of radicalism among young people poses a serious threat to social harmony and security in Indonesia. Islamic Religious Education (PAI) has a strategic role in protecting young people from the influence of radical ideologies through the instilling of values of moderation, tolerance, and inclusivity. This study uses a literature review method to examine theories, concepts, and previous research findings related to the role of PAI in preventing radicalism. The analysis focuses on the integration of Islamic values of moderation in the curriculum, the role of teachers as facilitators, challenges in implementing PAI, and solutions for optimising the role of religious education. The results of the study indicate that PAI is effective in shaping moderate character when supported by synergy between schools, families, and communities, as well as the strengthening of digital literacy. This study provides recommendations for curriculum development and educator competencies to optimise the role of PAI in preventing radicalism and maintaining religious harmony among youth.